Commandeering the mammalian Ago2 miRNA network: a newly discovered mechanism of helminth immunomodulation. Issue 12 (December 2021) - Donnelly, Sheila; Tran, Nham
Abstract : MicroRNAs (miRNAs) are a class of noncoding RNAs that contribute to a broad range of biological processes through post-transcriptional regulation of gene expression. Helminths exploit this system to target mammalian gene expression, to modulate the host immune response. Recent discoveries have shed new light on the mechanisms involved.